Adding pegylated interferon to entecavir for hepatitis B e antigen–positive chronic hepatitis B: A multicenter randomized trial (ARES study). Issue 5 (27th February 2015) - Brouwer, Willem Pieter; Xie, Qing; Sonneveld, Milan J.; Zhang, Ningping; Zhang, Qin; Tabak, Fehmi; Streinu‐Cercel, Adrian; Wang, Ji‐Yao; Idilman, Ramazan; Reesink, Hendrik W.; Diculescu, Mircea; Simon, Krzysztof; et al.
Abstract : Entecavir (ETV) is a potent inhibitor of hepatitis B viral replication, but long‐term therapy may be required. We investigated whether adding on pegylated interferon (Peg‐IFN) to ETV therapy enhances serological response rates. In this global investigator‐initiated, open‐label, multicenter, randomized trial, hepatitis B e antigen (HBeAg)‐positive chronic hepatitis B (CHB) patients with compensated liver disease started on ETV monotherapy (0.5 mg/day) and were randomized in a 1:1 ratio to either Peg‐IFN add‐on therapy (180 µg/week) from week 24 to 48 (n = 85) or to continue ETV monotherapy (n = 90). Response was defined as HBeAg loss with HBV DNA <200 IU/mL at week 48. Responders discontinued ETV at week 72. All patients were followed until week 96. Response was achieved in 16 of 85 (19%) patients allocated to the add‐on arm versus 9 of 90 (10%) in the monotherapy arm ( P  = 0.095). Adjusted for HBV DNA levels before randomized therapy, Peg‐IFN add‐on was significantly associated with response (odds ratio: 4.8; 95% confidence interval: 1.6‐14.0; P  = 0.004). Eleven (13%) of the add‐on‐treated patients achieved disease remission after ETV cessation versus 2 of 90 (2%) of those treated with monotherapy ( P  = 0.007), which was 79% (11 of 14) versus 25% (2 of 8) of those who discontinued ETV ( P  = 0.014). At week 96, 22 (26%) patients assigned add‐on versus 12 (13%) assigned monotherapy achieved HBeAg seroconversion ( P  = 0.036). Peg‐IFN add‐on led to significantly more decline in hepatitis B surface antigen, HBeAg, and HBV DNA (all P  < 0.001). Combination therapy was well tolerated. Conclusion : Although the primary endpoint was not reached, 24 weeks of Peg‐IFN add‐on therapy led to a higher proportion of HBeAg response, compared to ETV monotherapy. Add‐on therapy resulted in more viral decline and appeared to prevent relapse after stopping ETV. Hence, Peg‐IFN add‐on therapy may facilitate the discontinuation of nucleos(t)ide analogs. (Hepatology 2015;61:1512–1522)